Georg Lukács and Critical Theory Aesthetics, History, Utopia - Miller, Tyrus (Edinburgh University Press, 2023)
This book examines the heritage of critical theory from the Hungarian Marxist philosopher Georg Lukács through the early Frankfurt School up to current issues of authoritarian politics and democratisation. Interweaving discussion of art and literature, utopian thought, and the dialectics of high art and mass culture, it offers unique perspectives on an interconnected group of left-wing intellectuals who sought to understand and resist their society's systemic impoverishment of thought and experience. Starting from Lukács's reflections on art, utopia, and historical action, it progresses to the Frankfurt School philosopher Theodor W. Adorno's analyses of music, media, avant-garde and kitsch. It concludes with discussions of erotic utopia, authoritarianism, postsocialism, and organised deceit in show trials - topics in which the legacy of Lukács and Frankfurt School critical theory continues to be relevant today.